Odpowiedź :
Odpowiedź:
a) 1 i 1/4 -1/2 -3/8 + 1 i 5/8= 1 i 2/8 -4/8 -3/8 +1 i 5/8= 1 i 2/8 + 1 i 5/8- 7/8=
= 2 i 7/8- 7/8= 2
b) ( 7 i 3/5 -2 i 7/10) - ( 3 i 1/4 + 1 i 1/2)=
= ( 7 i 12/20 - 2 i 14/20)- ( 3 i 5/20 + 1 i 10/20) =
= ( 6 i 32/20- 2 i 14/20)- 4 i 15/20= 4 i 18/20 - 4 i 15/20= 3/20
c) 12 - ( 2 i 1/5 + 3 i 3/4)= 12 - ( 2 i 4/20+ 3 i 15/20)= 12 - 5 i 19/20=
=11 i 20/20- 5 i 19/20= 6 i 1/20
Szczegółowe wyjaśnienie:
Odpowiedź:
[tex]a)\ \ 1\frac{1}{4}-\frac{1}{2}-\frac{3}{8}+1\frac{5}{8}=\frac{5}{4}-\frac{1}{2}-\frac{3}{8}+\frac{13}{8}=\frac{5}{4}-\frac{1}{2}+\frac{10}{8}=\frac{10}{8}-\frac{4}{8}+\frac{10}{8}=\frac{16}{8}=2[/tex]
[tex]b)\ \ (7\frac{3}{5}-2\frac{7}{10})-(3\frac{1}{4}+1\frac{1}{2})=(7\frac{6}{10}-2\frac{7}{10})-(3\frac{1}{4}+1\frac{2}{4})=(6\frac{16}{10}-2\frac{7}{10})-4\frac{3}{4}=\\\\=4\frac{9}{10}-4\frac{3}{4}=4\frac{18}{20}-4\frac{15}{20}=\frac{3}{20}[/tex]
[tex]c)\ \ 12-(2\frac{1}{5}+3\frac{3}{4})=12-(2\frac{4}{20}+3\frac{15}{20})=12-5\frac{19}{20}=11\frac{20}{20}-5\frac{19}{20}=6\frac{1}{20}[/tex]